Development of Digital Student Worksheets (LKPD) on Properties of Solid, Liquid and Gas Objects for Class V Elementary Students - Juwantara, Ridho Agung; Harjanto, Ambyah; Febriana, Arivah Ena; Elvadola, Connyta (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This research aims to see the extent of the LKPD development process on the properties of solid, liquid and gas objects material in the 5th grade of elementary school, as well as finding out the results of the analysis regarding the feasibility and response to product implementation. This research uses the ADDIE model development method which involves questionnaires, tests and several interviews in data collection. The development of digital-based LKPD has very good feasibility. This can be seen from the material expert validity test of 3.8, the language expert test of 3.7, the media expert test of 3.9 and all of them are recommended as very valid and suitable for use. The development of digital-based LKPD has very good effectiveness in learning science material on the properties of solid, liquid and gas objects as assessed from the test results given. The posttest learning results achieved were very significant.